The effect of Critical Speed Training on Iron Responses and Lactic of Runners - Karrer Hussien fadhel; Dahham, Alyaa Haussien; Jassim, Mokhalad Muhammed (International Journal of Psychosocial Rehabilitation, 2020)
In the study, a critical swim speed (CSS) training program was put for runners using a rated equation. Also, study the effect of these training on iron and lactic responses. Running distances rated by extracting one-eighth of the real race distance and applying the equation according to the CSS principle. Training applied to a group of trained running men (17-18 years). The homogeneity of the sample considered using standard techniques. The iron, hepcidin , ferritin, interleukin-6 and lactic were measured. The results showed that there is a difference in all responses related to iron and lactic for post and pre-test (during rest and after effort). It was observed that there was an increase in the levels of hepcidin, lactic, interleukin-6 and iron after the effort, while the ferritin decreased after the effort. After 3 months of training and because of the adaptations, the levels of lactic, hepcidin and iron increased as well as the ferritin, and the percentage of interleukin-6 decreased. From the results, it became clear that all these changes were with the normal ranges